Perbandingan Latihan One Leg Diagonal Chop Dengan Single Leg Balance Twist Terhadap Peningkatan Keseimbangan Tubuh - Muhammad Iqbal Fauzan; Dede Iman Suhendra; Tony Hartono; Sri Maryati; Andang Rohendi; Hendra Rustiawan (Universitas Galuh, 2025)
The addition of performance to improve body balance of both leg muscles as the goal of training two independent variables, namely one leg diagonal chop and single leg balance twist. This study applied a pre-experimental design and used a two-group design plan given before and after training or treatment. The research location was at MAN 3 Ciamis Regency. The sample taken in this study were athletes aged 17-18 years totaling 20 male futsal extracurricular. The test instrument used was a standing stork test-blind. The statistical process used SPSS 26. This study resulted in: 1. one leg diagonal chop training has a significant effect on improving body balance. 2. Single leg balance twist training has a significant effect on improving body balance. 3. There is a significant difference between one leg diagonal chop training and single leg balance twist training on improving body balance. Conclusion: One Leg Diagonal Chop Training with Single Leg Balance Twist Training on Improving Body Balance and can be used as one of the recommended training for body balance.